Two-photon lithography and microscopy of 3D hydrogel scaffolds for neuronal cell growth. (16th February 2018) - Accardo, Angelo; Blatché, Marie-Charline; Courson, Rémi; Loubinoux, Isabelle; Vieu, Christophe; Malaquin, Laurent
Abstract: 3D fabrication techniques are rapidly expanding in the field of scaffold development for cell culture and tissue engineering. Herein we report the realization of free-standing PEGDA hydrogel architectures by using two-photon lithography. The morphological and immunofluorescence characterization of neuro2A cells revealed a tridimensional colonization featuring multiple neuritic extensions per cell as well as the expression of β -tubulin neuronal marker and actin microfilaments. The results open new perspectives in the continuous quest for structured biomaterials able to provide a favorable environment to cells and at the same time not interfering with imaging protocols necessary for a clear scenario of the cell seeding.